Differences in autonomic heart rate modulation during rest and after a supramaximal anaerobic test in relation to gender and the menstrual cycle in women - Andrić, Lana; Karan, Vedrana; Radulović, Nikola; Drapšin, Miodrag; Karaba Jakovljević, Dea; Takači, Aleksandar; Klašnja, Aleksandar (Vojnosanitetski pregled, 2021)
Background/Aim. Heart rate variability (HRV) and heart rate recovery (HRR) show differences between genders, and dissimilarities were also reported in women in various menstrual cycle (MC) phases. The aim of this research was to analyze cardiac autonomic indices during rest and in recovery after the Wingate test between genders in the young, sedentary population and to investigate whether a MC phase in women can influence these indices. Methods. Twenty-five females (20.5 ± 0.7 years) and sixteen males (20.4 ± 0.7 years) performed the Wingate anaerobic test on a cycle ergometer while their HRR and resting and recovery HRV indices were obtained. In females, data were collected during three distinctive MC phases. Results. The natural logarithm of low-frequency (lnLF) HRV marker and the natural logarithm of high-frequency (lnHF) HRV marker were higher in males during rest compared to women in all MC phases, except in the late follicular phase, where no differences in lnHF between genders were observed. Markedly higher lnLF and lnHF were recorded in males after the Wingate test. There were no differences in HRV between women in various MC phases during rest. Surprisingly, parasympathetic time-domain marker (the square root of the mean squared differences of successive NN intervals, RMSSD) and lnLF were both higher in the early follicular phase in comparison to the luteal phase of MC during recovery. HRR was faster in men in comparison to women in all MC phases. Conclusion. Males show greater HRR and total variability during rest and recovery, but it appears that resting parasympathetic activity is similar when females are in the late follicular phase of MC. Intra-female resting autonomic variability is not affected by the sex hormonal cycle. Post-exercise HRV in the early follicular phase reflects a significantly favourable autonomic profile in comparison to the luteal phase of MC.